Development of Digital-Based Comics on National Insight Material in Class V of SD Negeri 105410 Rampah Pekan - Sari, Muti Indah; Dahnial, Irfan (Syntax Corporation, 2024)
Education is one aspect that is influenced by developments in technology, information and communication. For example, a shift in learning paradigms to accommodate advances in science and technology to increase efficiency and optimize learning. The development of the educational era indirectly requires teachers to be able to utilize technology, information and communication as media and teaching materials for learning activities. The aim of developing digital-based comic learning media is that it is considered to be able to help students understand learning material because the advantage of digital-based comic media is that it is able to present images that can arouse students' interest in learning. This type of development research uses the 4D model which was initiated by Thiagarajan (1974). This 4D development model has four stages, namely define, design, develop and desseminate, but in development research it only reaches the develop stage. The product that has been developed by this researcher has been validated by material experts getting 81.66% percentage with the criteria